2011
DOI: 10.1021/ic200371a
|View full text |Cite
|
Sign up to set email alerts
|

Freezing in Resonance Structures for Better Packing: XeF2 Becomes (XeF+)(F) at Large Compression

Abstract: Recent high-pressure experiments conducted on xenon difluoride (XeF(2)) suggested that this compound undergoes several phase transitions up to 100 GPa, becoming metallic above 70 GPa. In this theoretical study, in contrast to experiment, we find that the ambient pressure molecular structure of xenon difluoride, of I4/mmm symmetry, remains the most stable one up to 105 GPa. In our computations, the structures suggested from experiment have either much higher enthalpies than the I4/mmm structure or converge to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 54 publications
(48 reference statements)
8
43
1
Order By: Relevance
“…Even compounds as exotic as XeF 2 , with its hypervalent F-Xe-F bonding, have been calculated to undergo transformation to the ionic (XeF) + F À polymorph at sufficiently high pressures. 168 This process is analogous to what is observed in acidic environments (for example, addition of SbF 5 Lewis acid to XeF 2 leads to the formation of (XeF) + salt), but predicted here to take place by the application of pressure alone. 168 …”
Section: Predictions For Experimentssupporting
confidence: 72%
See 1 more Smart Citation
“…Even compounds as exotic as XeF 2 , with its hypervalent F-Xe-F bonding, have been calculated to undergo transformation to the ionic (XeF) + F À polymorph at sufficiently high pressures. 168 This process is analogous to what is observed in acidic environments (for example, addition of SbF 5 Lewis acid to XeF 2 leads to the formation of (XeF) + salt), but predicted here to take place by the application of pressure alone. 168 …”
Section: Predictions For Experimentssupporting
confidence: 72%
“…168 This process is analogous to what is observed in acidic environments (for example, addition of SbF 5 Lewis acid to XeF 2 leads to the formation of (XeF) + salt), but predicted here to take place by the application of pressure alone. 168 …”
Section: Predictions For Experimentssupporting
confidence: 72%
“…We find that F-Kr-F molecules in KrF 2 undergo slight bending in response to compression, in analogy to ArF 2 , but we do not encounter any signs of auto-ionization, as predicted for XeF 2 [42]. Interestingly, our structure searches do not identify any phases containing KrF + and Kr 2 F 3 + cations, which are known to form upon reaction of KrF 2 with fluoride acceptors [7].…”
Section: Discussionsupporting
confidence: 47%
“…Values close to 1 are generally interpreted as indicating paired electrons (i.e., lone pairs, bonds, and core electrons). Typical covalent bonds are characterized by ELF values of exceeding 0.7; however, previous studies indicated that the maximum ELF value for the Xe-F bond in XeF 2 is only 0.5 [42,44]. This can be rationalized by taking into account that this bond arises from a three-center two-electron interaction, and is characterized by a bond order of 1/2.…”
Section: Pressures Up To 50 Gpamentioning
confidence: 95%
See 1 more Smart Citation